War past, present & future - Black, Jeremy (Sutton Publishing Limited, 2000)
Offers a far-reaching assessment of military history, challenging the focus on technology and military revolution. War is placed in context, from the evolution of specialised troops in the earliest civilisations, to likely future scenarios.